Determination of protective effectiveness of nerium oleander distillation in doxorubicin-induced organ damages - Burak Dik; Ayşe Er; Orhan Çorum (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate that effect of Nerium oleander (NO) distillate on doxorubicin-induced oxidative damage and other side effects. Materials and Methods: NO leaves were collected, distillated and lyophilized. In the current research, 28 rats were divided into 4 groups; Control, Doxorubicin (3 mg/kg, every other day, intraperitoneally), NO (1 mg/kg, SID, PO) and Doxorubicin (3 mg/kg, every other day, intraperitoneally) + NO (1 mg/kg, SID, PO). All treatments were performed 11 days. At 24 hours after the last administration, blood samples were taken from the hearts under general anesthetizes, and euthanized immediately. Also, heart, liver and kidney were taken and homogenized. Tissue thiobarbituric acid reactive substances (TBARS) levels, serum biochemical and hemogram values were measured by ELISA, autoanalyzer and blood cell counter, respectively. Results: Heart TBARS values of the doxorubicin group were lower (P<0.05) than Doxorubicin + NO distillate group, while kidney TBARS values of the doxorubicin group were higher (P<0.05) than the NO distillate group. Although doxorubicin decreased (P<0.05) blood cell counts, hemoglobin and hematocrit levels compared to Control group, administration of doxorubicin + NO distillate ameliorated only hematocrit levels. Doxorubicin decreased (P<0.05) serum total protein and albumin levels compared to Control group, while Doxorubicin + NO distillate increased (P<0.05) aspartate aminotransferase and blood urea nitrogen levels and decreased (P<0.05) total protein, albumin and creatinine levels. Conclusions: It may be stated that levels of NO distillate used in the current research do not prevent the doxorubicin caused side effects.